Mariano García, María José Punte y María Lucía Puppo (comps.), Espacios, imágenes y vectores: desafíos actuales de las literaturas comparadas, Buenos Aires, Miño y Dávila Editores, 2015, 256 pp. - Cid, Adriana Cecilia (2017)
Fil: Cid, Adriana Cecilia. Pontificia Universidad Católica Argentina; Argentina